Identification of factors involved in Enterococcus faecalis biofilm under quercetin stress. (January 2019) - Qayyum, Shariq; Sharma, Divakar; Bisht, Deepa; Khan, Asad U.
Abstract: Enterococcus faecalis is a gram positive enteric commensal bacteria or opportunistic pathogen and its infection involves biofilm formation. Quercetin, a plant origin polyphenol was found to inhibit E. faecalis biofilm. Crystal violet assay, SEM and CLSM microscopy confirmed biofilm inhibition by quercetin. Proteomics was used to elucidate the changes occurred in bacterial cell by quercetin treatment. 2D-Electrophorosis and MALDI-TOF analysis revealed that nineteen proteins were differentially expressed in quercetin treated sample. Glycolytic pathways, protein translation-elongation pathways and protein folding pathways were under differential expression after treatment. Real Time-PCR (RT-PCR) validated the proteomic data at genomic level except for the translation elongation factor G which showed opposite data to proteomics. Protein-protein interaction networks constructed using STRING 10.0 demonstrated strong connection of translation-elongation proteins with many important proteins. The results of the comparative analysis indicate that quercetin exerts its inhibitory effect by disturbing glycolytic, protein translation-elongation and protein folding pathways. This disturbs bacterial physiology and stops transition of planktonic cells to biofilm state. Highlights: Quercetin was observed to inhibit the biofilm of E. faecalis at sub-MIC concentrations. Proteome of E. faecalis under quercetin stress was analyzed by 2DE and MALDI-TOF/MS. 19 proteins were differentially expressed after quercetin treatment. Translation-elongation proteins might be involved in biofilm formation.